PKM Upaya Deteksi Dini Dampak Penggunaan Gadget pada Remaja terhadap Masalah Psikologis - Dea Muspratiwi; Mawar Eka Putri; Syamilatul Khariroh; Komala Sari; Linda Widiastuti; Yusnaini Siagian; Utari Yunie Atrie (Jurnal Medika: Medika, 2026)
The use of gadgets among school adolescents has increased significantly and has the potential to cause various psychological problems such as anxiety, sleep disturbances, decreased social interaction, and impaired learning concentration. This community service activity aimed to conduct early detection of adolescent mental health problems and improve students’ knowledge regarding healthy and wise gadget use. The implementation methods included health education, interactive discussions, question-and-answer sessions, mental health screening using questionnaires, and pre-test and post-test evaluations. The activity was conducted among school students in the community health center working area. The screening results showed that most students had relatively good mental health conditions, where 80% of students did not frequently feel anxious or worried, 76% did not experience overthinking, and 87% did not feel sad or depressed. In addition, there was an improvement in students’ knowledge after receiving mental health education and healthy gadget use education. The percentage of students with high scores increased from 76.5% in the pre-test to 90% in the post-test. Mental health screening and educational activities proved effective as promotive and preventive efforts in increasing adolescents’ awareness of the impact of gadget use on mental health.